2020
DOI: 10.2147/lra.s288726
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Different Doses of Intravenous Dexmedetomidine on the Properties of Subarachnoid Blockade: A Systematic Review and Meta-Analysis</p>

Abstract: Background Dexmedetomidine is a sedative and analgesic medication which has gained an increased usage as an adjuvant to both general and regional anaesthesia in recent years. In this systematic review and meta-analysis, we examined the changes to the characteristics of subarachnoid block when accompanied with intravenous dexmedetomidine. Our aim is to evaluate the effects of different doses of intravenous dexmedetomidine on the sensory and motor blockade duration of a single shot spinal anaestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This cost will be over and above the cost of analgesic drug which will be used in any case after 20-40 min in such scenerio. [4,5,6] The adverse effects observed with the use of these drugs in our study were statistically insignificant, as also reported by Jaung et al in their metaanalysis of 14 studies. [7] The most common reported adverse effects in other studies are bradycardia and hypotension but usually these were mainly related to its intravenous use as infusion in the elderly and in patients with pre-existent cardiac disease.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…This cost will be over and above the cost of analgesic drug which will be used in any case after 20-40 min in such scenerio. [4,5,6] The adverse effects observed with the use of these drugs in our study were statistically insignificant, as also reported by Jaung et al in their metaanalysis of 14 studies. [7] The most common reported adverse effects in other studies are bradycardia and hypotension but usually these were mainly related to its intravenous use as infusion in the elderly and in patients with pre-existent cardiac disease.…”
Section: Introductionsupporting
confidence: 88%
“…This cost will be over and above the cost of analgesic drug which will be used in any case after 20-40 min in such scenerio. [2,3,4]…”
mentioning
confidence: 99%
“…23,24 Studies have reported good analgesic effect with this dose range, although few studies reported bradycardia, hypotension and sedation with dose of 1-2 mcg/kg. 25,26 So we stick to the dose of 0.5 mcg/kg which resulted in good postoperative analgesia with median VAS of 2. None of the patients in our study had bradycardia, hypotension or sedation in the intraoperative or postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Using Dexmedetomidine in ESPB decreased VAS and analgesic consumption in the postoperative period when compared to plain ropivacaine without any adjunct (10) . Few studies reported bradycardia, hypotension and sedation with dose of 1-2 mcg/kg (11) .…”
Section: Resultsmentioning
confidence: 99%